Orthodontıc Approach In Tmj Cases After Early Perıod Surgıcal Operatıon - Tuba Tortop Üçem; Sema Yüksel; Ahmet Çanga (Galenos Yayinevi, 1995)
Three bilateral temporamandibular joint ankylosis cases were observed for one year after an early period surgical operation. Two of them were used hybrid appliances in order to stimulate the growth on the affected side and to correct facial asymmetry.